Evaluation of Antineoplastic Delayed-Type Hypersensitivity Skin Reactions In Vitro - Inés Roger; Paula Montero; Antonio García; Javier Milara; Pilar Ribera; Jose Alejandro Pérez-Fidalgo; Julio Cortijo (MDPI AG, 2022)
Delayed-type hypersensitivity (DTH) is caused by a broad number of drugs used in clinic, and antineoplastic drugs show an elevated proportion of DTH, which potentially affects the quality of life of patients. Despite the serious problem and the negative economic impact deriving from market withdrawal of such drugs and high hospitalization costs, nowadays, there are no standard validated methods in vitro or in vivo to evaluate the sensitizing potential of drugs in the preclinical phase. Enhanced predictions in preclinical safety evaluations are really important, and for that reason, the aim of our work is to adapt in vitro DPRA, ARE-Nrf2 luciferase KeratinoSensTM, and hCLAT assays for the study of the sensitizing potential of antineoplastic agents grouped by mechanism of action. Our results reveal that the above tests are in vitro techniques able to predict the sensitizing potential of the tested antineoplastics. Moreover, this is the first time that the inhibition of the VEGFR1 pathway has been identified as a potential trigger of DTH.